Kinetic study of the dissolution of metakaolin with hydrofluoric acid - Pinna, Eliana Guadalupe (2018)
The kinetics mechanism on the dissolution of metakaolin by hydrofluoric acid has been studied. The effects of temperature, reaction time, and stirring speed have been examined. Experimental results show that reaction rate increases with both temperature and reaction time. The global process of metakaolin dissolution with HF is characterized with an apparent activation energy of 21.096 kcal/mol, which indicates that the reaction rate is mainly controlled by the chemical stage. Experimental data fitted the sequential nucleation and growth model.